Strategi Pemasaran Ekspor Ikan Tuna Beku (Studi Kasus di PT Danaumatano Persada Raya Jakarta) - Iis Diatin (Buletin Ekonomi Perikanan, 1996)
The research was conducted to examine the marketing strategic to find the alternatif solution that can be applied to solve the problem. The reserch to catod at PT Danaumatano Persada Raya Jakarta.The method is case study, with SWOT analysis to solve the problem.The result of SWOT  analysis indicated that strategic were:SW : new market segmen, develop the product and new market.ST : market research, resuorse efficiency and training of the human resourcesWO : recruitment of the marketing expert, human resurc e efficiency and promotion.WT : basic price selling and market breakthrough.The altematif strategic : to develop the new market, resource efficiency recruitment of the marketing expert and market breakthrough.